Mellem tanke og billede – om Henrik Nordbrandts bidrag til 1900-tallets metafordebat - Błaszczyk, Aldona (Folia Scandinavica Posnaniensia, 2010)
The article departs from the 20th century's academic discussion devoted to the notion of metaphor. The discussion has developed two contradictory claims concerning the role of metaphors in language. One of them considers metaphor as a linguistic decoration or ornament of poetry, whereas the other one enhances its visional and cognitive properties. In the light of this argument, the article presents the development in the use of metaphors throughout the works of one of the most prominent contemporary Danish poets, Henrik Nordbrandt. Henrik Nordbrandt's deeply reflective approach to the role of metaphor has notably marked his poetry since his debut in 1966 until today. The article investigates the use of metaphors in several poems selected from 3 successive phases in Nordbrandt's poetic career. On the basis oft his study the author attempts to point out the major changes in Henrik Nordbrandt's nderstanding of the role of metaphors in poetry, as well as define his general contribution to the mentioned discussion on the properties of metaphors.